Design Development and Performance Evaluation of Two-Row Corn Seed Planter - Ansar, Ansar; Nazaruddin, Nazaruddin; Azis, Atri Dewi (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2023)
One of the main requirements for small-scale cultivators is that they can be used in small plots of land and have simple design and technology. However, many planting tools on the market today are not suitable for narrow land conditions. Therefore, this study aims to design and develop a corn seed planter that can be operated in narrow areas and can improve seed planting efficiency and accurate seed placement. The research parameters observed were the distance between plants, the depth of the planting holes, the number of seeds per planting hole, and the efficiency of using the tool. The results of the research show that the planting tools that have been designed and developed are very easy and practical to operate by farmers on narrow land. The distance between plants varies between 21.3 – 24.2 cm. The depth of the planting hole ranges from 5.4 – 7.1 cm. The distribution of the number of holes filled with 0 seeds was 3.00%, filled with 1 seed was 90.38%, and filled with 2 seeds was 6.62%. Planter efficiency data is 85.61%. This data shows that this cultivator meets the minimum standards for the manually operated cultivator category. Keywords: Distance between seeds, Efficiency, Empty hole, Land productivity, Planting hole.